Quizizz as an Interactive Learning Tool to Improve Students’ Interest in Learning English - Wulandari, Ervina Eka; Jati, Sigit Pramono; Nikmah, Lailatun (ICONELT, 2024)
Quizizz is an online platform that offers a variety of creative learning to make the classroom more fun. This research was conducted with the aim of exploring students’ views on using Quizizz as an interactive learning tool in learning English. This is qualitative research involving in-depth interviews. In this study, the researcher used a qualitative approach by conducting semi-structured interviews as a data collection technique. The subjects of this research were taken from five eighth-grade students based on their experience in using Quizizz as an English learning. The results of these findings indicate that the use of Quizizz significantly increases students’ interest in learning English. This is based on student perception, stating that gamification features such as leaderboards, point systems, and fast feedback create a more fun and challenging learning atmosphere. Apart from that, the Quizizz feature is also considered capable of fostering social interaction and healthy competition, as well as motivating students to participate more actively and deeply in learning activities. These results indicate that game-based learning tools, such as Quizizz, can be implemented as an effective tool to encourage students’ interest and enthusiasm in learning English.